An investigation of the implications of lunar illumination spectral changes for Day/Night Band‐based cloud property retrieval due to lunar phase transition. Issue 17 (8th September 2017) - Min, Min; Deng, Jianbo; Liu, Chao; Guo, Jianping; Lu, Naimeng; Hu, Xiuqing; Chen, Lin; Zhang, Peng; Lu, Qifeng; Wang, Ling
Abstract: The Moon reflects sunlight like a huge mirror hanging in the sky at night, which presents the obviously periodical changes in its luminance or irradiance due to Sun‐Earth‐Moon geometry variation. The potential effect of the periodical changes in lunar phase angle on nighttime Day/Night Band (DNB) radiative transfer simulation in the presence of cloud has seldom been reported thus far. In this study, a radiative transfer model is developed by coupling the lunar light source with various Sun‐Earth‐Moon geometries. To elucidate the stability of DNB‐averaged cloud bulk scattering properties, we simulate nighttime reflectance and radiances under four typical lunar phase angles (0°, 45°, 90°, and 135°) from 7 April 2016 to 8 May 2016 (e.g., two lunar cycles). Explicit simulation analyses indicated that DNB‐averaged cloud bulk scattering properties exhibit weak sensitivity to lunar phase angles. The maximum DNB reflectance differences between any and 90° lunar phase angles are less than 0.05% (0.01%) in the presence of water (ice) clouds, indicating a negligible effect of periodically changes on lunar spectral irradiances. Our findings suggest that the differences of reflectance at lunar phase angle = 90° are less than approximately 0.05% (water cloud)/0.01% (ice cloud), much smaller than 11% radiometric calibration uncertainties of DNB. This means that these differences could be ignored in both nighttime cloud property retrieval and DNB radiative transfer modeling. Key Points: The DNB‐averaged bulk cloud scattering properties do not vary considerably with different lunar phase angles The maximum DNB reflectance differences between any and 90{degree sign} lunar phase angles are less than 0.05% (0.01%) for water (ice) cloud The periodical changes in lunar spectral irradiances exert a minor effect on DNB radiative transfer calculations under cloudy conditions